Exploration and Measurement of Students' Critical Thinking Skills Through the ELPSA Model Integrated with Math City Map in Real Environments - Robial, Robial; Sunismi, Sunismi; Fuady, Anies (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to explore and measure students' mathematical critical thinking skills through the ELPSA (Experience, Language, Pictorial, Symbolic, Application) learning model integrated with Math City Map (MCM). Using Mixed methods with a sequential explanatory design involving 130 MTsN students in Sarolangun Regency, who were divided into experimental and control classes. Quantitative data were collected through pretests and posttests, while qualitative data were gathered through observation, interviews, and field notes. Through the independent sample t-test, the posttest score of the experimental class (M = 65.68; SD = 14.231) was higher than the control class (M = 52.98; SD = 11.737) with a 2-tailed Sig. <0.001 and a large effect size (Cohen's d = 0.973). Qualitative analysis strengthens these findings by showing increased engagement, courage to express opinions, and students' ability to provide logical reasons. The synergy of ELPSA and MCM has been proven to provide contextual, interactive, and meaningful learning, thus encouraging students to be more active in critical thinking. Further research is recommended to expand the context and educational levels to assess the consistency of the ELPSA model integrated with Math City Map at various cognitive levels.